2012
DOI: 10.1002/jcb.24386
|View full text |Cite
|
Sign up to set email alerts
|

Platycodin D induces anoikis and caspase‐mediated apoptosis via p38 MAPK in AGS human gastric cancer cells

Abstract: Mitogen-activated protein kinases (MAPKs) cascades play important roles in cell proliferation, death, and differentiation in response to external stimuli. However, the precise role of MAPKs in platycodin D (PD)-induced cytotoxicity remains unclear. In this study, we investigated the anticancer effect of PD and its underlying mechanism on AGS human gastric cancer cells. PD significantly inhibited cell proliferation and induced anoikis, which is a form of apoptosis in which cells detach from the substrate. It sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 51 publications
(37 reference statements)
6
72
0
Order By: Relevance
“…The inhibition of the activation of the p38 signal transduction pathway can induce apoptosis (28). p38 MAPK could promote apoptosis of lung adenocarcinoma cells via the regulation of the expression of the apoptosis-related proteins Bax and Bcl2 (29).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of the activation of the p38 signal transduction pathway can induce apoptosis (28). p38 MAPK could promote apoptosis of lung adenocarcinoma cells via the regulation of the expression of the apoptosis-related proteins Bax and Bcl2 (29).…”
Section: Discussionmentioning
confidence: 99%
“…Platycodin D (PD) is a triterpenoid saponin isolated from the Chinese medicinal herb Platycodonis Radix. It possesses important biological activities, including immune stimulation (Xie et al, 2008), anti-inflammation (Kim et al, 2001Ahn et al, 2005), anti-nociception (Choi et al, 2002), anti-obesity Lee et al, 2010), anti-atherosclerosis (Wu et al, 2012) and anti-cancer (Kim et al, 2005Kim et al, 2008a;Kim et al, 2008b;Shin et al, 2009;Choi et al, 2010;Yu and Kim, 2010;Chun et al, 2012) etc. Due to the various pharmacological activities, PD has been listed as the marker for the quality control of Platycodonis Radix in the Pharmacopoeia of the People's Republic of China (Pharmacopoeia Commission of the Ministry of Health of the P.R.…”
Section: Introductionmentioning
confidence: 99%
“…As the most abundant triterpenoid saponin derived from the roots of Platycodin grandiflorum, Platycodin D (PD), has been reported to show a wide range of health benefits, such as anti-atherosclerotic (4), anti-inflammatory (5,6), hypocholesterolemic and anti-obesity effects (7). Previous studies have shown that PD has obvious anticancer activity against different human malignant cancer cells both in vitro (10,11,13,14,16,17) and in vivo (9,12,15).…”
Section: Discussionmentioning
confidence: 99%
“…Platycodin D (PD), a triterpenoid saponin derived from the roots of Platycodin grandiflorum, has been reported to possess a wide rangeof health benefits, such as anti-atherosclerotic (4), anti-inflammatory (5,6), hypocholesterolemic, and anti-obesity effects (7), as well as spermicidal and contraceptive activity (8). Among the various health benefits of PD, anticancer effects have been noted in several cancer cell lines, including lung cancer cells (9), hepatocellular carcinoma cells (10), gastric cancer cells (11), prostate cancer cells (12), and leukemia cells (13,14). PD has also been reported to inhibit the viability of human breast cancer cells in vitro (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%